2004
DOI: 10.1007/s00167-004-0531-7
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondral lesion located at the lateral femoral condyle reconstructed by the transplantation of tissue-engineered cartilage in combination with a periosteum with bone block: a case report

Abstract: We report herein the successful treatment of a patient with an osteochondral defect extending to the edge of the lateral femoral condyle by transplantation of tissue-engineered cartilage made ex vivo using atelocollagen gel covered by periosteum with a bone block to reconstruct the normal contour of the femoral condyle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…2 Numerous preclinical studies and some clinical successes indicated that these tissue engineering approaches are scientifically practical. [3][4][5] However, restricted by high cost and complexity of production, the tissue engineering products have not yet been commercially effective. 6 These issues may retain tissue engineering as a costly and exclusive treatment for those who can afford.…”
Section: Introductionmentioning
confidence: 99%
“…2 Numerous preclinical studies and some clinical successes indicated that these tissue engineering approaches are scientifically practical. [3][4][5] However, restricted by high cost and complexity of production, the tissue engineering products have not yet been commercially effective. 6 These issues may retain tissue engineering as a costly and exclusive treatment for those who can afford.…”
Section: Introductionmentioning
confidence: 99%
“…8,30,31 Biphasic grafts, hyaluronan and polyester-based scaffolds, biochemically treated mesenchymal progenerator cells, and the tissue engineered osteochondral substitutes, although quite promising, are considered investigational. 1,7,14,22,25,34,[44][45][46]49,51,52,55,57,58 Osteochondral allograft transplantation (OCA) is appealing because it provides the ability to resurface larger and deeper defects with mature hyaline articular cartilage and addresses the underlying bone deficit in a single procedure. The appropriate size and surface contour can be matched when the graft is obtained from an appropriately selected organ donor.…”
mentioning
confidence: 99%
“…Randomized clinical trials have been performed, showing that this technique is superior to microfracture and as good or better than ACI in small to medium lesions [35, 55, 64], whereas doubts remain for bigger lesions. Adachi et al [2] documented a case report where lateral compartment postmeniscectomy OA in a 14‐year‐old girl was successfully treated with concurrent tissue‐engineered cartilage for a femoral lesion and OAT for a tibial lesion. Kock et al [74] treated a medial femoral condyle (MFC) lesion in a 43‐year‐old man with a dysfunctional reconstructed ACL and mild degenerative changes of the lateral compartment, with only an initial improvement and a failure after 3 years.…”
Section: Resultsmentioning
confidence: 99%